Analysis of Collaboration Between Rural Banks and Fintech Lending - Asi, Hot; Gularso , Kurnadi (CV. Publikasi Indonesia, 2023)
Fintech Lending or Information Technology-Based Joint Funding Services (LPBBTI) is a form of technological innovation in financial services that provides new alternatives for people to get access to loans in an easy and fast way. Fintech lending provides loans to individuals and businessmen who previously had difficulty obtaining loans from traditional financial institutions. The fintech lending industry enters the same market as banking to serve the community so that they can compete or collaborate with each other. Fintech lending and banks have their own characteristics and advantages so they have the potential to provide added value and reduce risk. The aim of this research is to analyze whether collaboration between Rural Banks (BPR) and fintech lending can be mutually beneficial and an optimal form of collaboration. This research was conducted from a case study of PT Duha Madani Syariah as a fintech lending provider in collaboration with 4 (four) BPRs. The research method used a qualitative approach. Data collected through observation, interviews, documentation, and triangulation techniques. The research results show that the collaboration between BPR and fintech lending is mutually beneficial for the parties because it increases loan disbursement, creates company operational efficiency, and increases company profits. This collaboration is outlined in a cooperation agreement which regulates the scope of mutually beneficial cooperation, and requires support from regulators through policies or implementing instructions to accelerate and improve collaboration between BPR and fintech lending